HUBUNGAN DINAMIKA KELOMPOK DENGAN PARTISIPASI ANGGOTA KELOMPOK WANITA TANI DALAM PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KECAMATAN TASIKMADU KABUPATEN KARANGANYAR - Puji Nurcahyanti; Eny Lestari; Sutarto Sutarto (AGRITEXTS: Journal of Agricultural Extension, 2017)
This study have a purpose to examine the level of group dynamics, the level of participation of women farmers group members farmers in the Region Sustainable Food House program and to examine the correlation between the level of group dynamics with participation of women farmers group members in the RSFH program. The basic method of study is descriptive quantitative with survey techniques. The study location is in Sub District of Tasikmadu Karanganyar Regency. The sampling method is using proportional random sampling with 60 respondents. The data analysis is used method of Rank Spearman correlation analysis. The results showed that the level of group dynamics in the dynamic category, and the level of participation of women farmers group members in the RSFH program in the active category. There is a significant correlation between the level of group dynamics, group building and maintenance, group cohesiveness and group atmosphere with a participation level of women farmers at the 99% trust levels; there is a significant correlation between the group goals, group structure, task function and group effectiveness with a participation level of women farmers at the 95% trust levels; and there is no significant correlation between group pressure and a hidden agenda with the participation level of women farmers group members in the RSFH program in Sub District of Tasikmadu Karanganyar Regency.